Do Personality Traits Moderate the Relationship between Mindfulness and Satisfaction with Life? - Biro, Filip; Popov, Boris (Psihološka istraživanja, 2025)
The aim of this study is to investigate the relationship between mindfulness and life satisfaction, while also examining whether personality traits moderate this relationship. The sample consisted of 214 respondents (158 females and 56 males, the average age of 29). The instruments used in the research include the following: Velikih pet + dva, skraćena verzija (Big Five + Two, shortened version), The Mindful Attention and Awareness Scale (MAAS), and Satisfaction with Life Scale (SWLS). The results indicate that mindfulness significantly predicts satisfaction with life. In spite of the fact that almost all personality traits correlate with mindfulness, no significant moderating effect of personality traits has been obtained regarding the relationship between mindfulness and satisfaction with life.
Keywords: mindfulness; satisfaction with life; personality traits